Training in innovative technologies for close-range sensing in Alpine terraine - Rutzinger, Martin; Anders, Katharina; Bremer, Magnus; Höfle, Bernhard; Lindenbergh, Roderik; Oude Elberink, Sander; Pirotti, Francesco; Scaioni, Marco; Zieher, Thomas (XXIV ISPRS Congress, Commission V and and Youth Forum, 2020)
The 3rd edition of the international summer school “Close-range Sensing Techniques in Alpine terrain” took place in Obergurgl, Austria, in June 2019. This article reports on results from the training and seminar activities and the outcome of student questionnaire survey. Comparison between the recent edition and the past edition in 2017 shows no significant differences on the level of satisfaction on organizational and training aspects. Gender balance was present both in candidates and in the outcome of selections. Selection was based on past research activities and on topic relevance. The majority of trainees were therefore doctoral candidates and postdoctoral researchers, but also motivated master students participated. The training took place through keynotes, lectures, seminars, in the field with hands-on surveys followed by data analysis in the lab, and teamwork for preparing a final team presentation over different assignments.